Acrylamide-induced disturbance of the redox balance in the chick embryonic brain. Issue 8 (3rd August 2017) - Batoryna, Marta; Lis, Marcin; Formicki, Grzegorz
ABSTRACT: This study was undertaken to determine the redox balance in the developing brain after exposure to acrylamide (ACR), a potent neurotoxin. The studies were performed using an in ovo chick embryo model. The antioxidant enzymes SOD, GPx, CAT, and reduced glutathione (GSH) were used as indicators of the redox balance. Eggs were injected with ACR doses of 40 mg kg −1 egg mass (2.4 mg egg −1 ) on embryonic day 17 (E17). The activity of the antioxidant enzymes and the concentration of GSH were measured at E17, E18, and E19 in the medulla oblongata, cerebrum, cerebellum, and optic lobe. The results indicated a significant decrease in the GSH concentrations in the optic lobe (E19, E20) and cerebrum (E20) of embryos exposed to ACR. The activities of SOD and GPx were significantly increased in the majority of the examined structures after injection of ACR. CAT activity was completely inhibited in the brains of the embryos exposed to ACR compared to that in the brains of the control embryos. Thus, we concluded that ACR exerts a significant influence on the redox balance in the developing brain by impacting the activity of antioxidant enzymes and the levels of GSH.